유리섬유복합소재를 이용한 지중매설형 승하강식 홍수방지 벽체구조물 - 윤영만 (한국재난정보학회 논문집, 9(4), 2013)
제방 월류방지 대체공법으로 전도식, 부력식 홍수방지벽을 국내ㆍ외에서 개발하는 실정이다. 그러나, 사전점검 불가 및 유지관리 문제점이 있어 본 연구에서는 국내ㆍ외 최초로 경량 재질이면서 강도가 우수한 유리섬유복합소재를 이용한 승하강식 홍수방지 벽체구조물을 연구ㆍ개발하였다. 개발된 홍수방지 벽체구조물은 수치해석을 통해 구조적 안정성과 함께 현장 적용성을 제시하여 공사비를 약 87%~95%로 감소시키고 벽체구조물 내부에 고무지수부재를 설치하여 차수성이 확보되는 것을 확인하였다. Walls for preventing floods using overturning or buoyancy method have been developed as replacement construction for preventing floods in and outside country. However, as they have some problems with pre-inspection and maintenance control, Eco-moving wall structure for preventing floods was studied and first developed using Glass Fiber Reinforced Composite which has not only light weight but outstanding strength. The developed wall structure for preventing floods offering structural stability and field applicability through numerical analysis was confirmed to reduce construction expenses by around 87~95% and secure waterproof property with the inside of the wall installed rubber water stopper. KCI Citation Count: 0